Tropical mammal functional diversity increases with productivity but decreases with anthropogenic disturbance. Issue 1945 (17th February 2021) - Gorczynski, Daniel; Hsieh, Chia; Luciano, Jadelys Tonos; Ahumada, Jorge; Espinosa, Santiago; Johnson, Steig; Rovero, Francesco; Santos, Fernanda; Andrianarisoa, Mahandry Hugues; Astaiza, Johanna Hurtado; Jansen, Patrick A.; Kayijamahe, Charles; et al.
Abstract : A variety of factors can affect the biodiversity of tropical mammal communities, but their relative importance and directionality remain uncertain. Previous global investigations of mammal functional diversity have relied on range maps instead of observational data to determine community composition. We test the effects of species pools, habitat heterogeneity, primary productivity and human disturbance on the functional diversity (dispersion and richness) of mammal communities using the largest standardized tropical forest camera trap monitoring system, the Tropical Ecology Assessment and Monitoring (TEAM) Network. We use occupancy values derived from the camera trap data to calculate occupancy-weighted functional diversity and use Bayesian generalized linear regression to determine the effects of multiple predictors. Mammal community functional dispersion increased with primary productivity, while functional richness decreased with human-induced local extinctions and was significantly lower in Madagascar than other tropical regions. The significant positive relationship between functional dispersion and productivity was evident only when functional dispersion was weighted by species' occupancies. Thus, observational data from standardized monitoring can reveal the drivers of mammal communities in ways that are not readily apparent from range map-based studies. The positive association between occupancy-weighted functional dispersion of tropical forest mammal communities and primary productivity suggests that unique functional traits may be more beneficial in more productive ecosystems and may allow species to persist at higher abundances.